The Correlation of Junior High School Students’ Speaking Anxiety and Their Speaking Performance - Ferindah Heny Nurjayanti (Universitas Negeri Surabaya, 2024)
Speaking anxiety is a psychological phenomenon that can affect a person’s ability to convey thoughts and ideas orally. Meanwhile, speaking ability is the main skill in communication. The aim of this study to determine the relationship between students’ speaking anxiety and the speaking performance of state junior high school students. The research method used was a correlation study with a sample of 36 seventh-grade students at one of the State Junior high School in Lamongan. The data collection technique used a questionnaire adapted from Horwitz to determine students’ speaking anxiety levels and a student speaking test was used to determine students’ speaking performance. The results of data analysis using IBM SPSS Statistics 26 showed a correlation coefficient of r=-.402 and a significance value of 0.015. Based on these data, the results of this study indicate that there was a negative relationship at moderate level between students; speaking anxiety and students’ speaking performance. In addition, it was also found that most of the students experienced a level of anxiety about speaking at an anxious level.